Effect of high voltage pulsed current on pain and strength of back muscles in patients with back problems: A randomized controlled study [Bel problemli hastalarda yüksek voltaj kesikli akimin aǧri ve bel kas kuvvetine etkisi: Rastgele kontrollü çalişma] - (:unkn) unknown (My University, 2010)
Purpose: The aim of this study was to evaluate the effectiveness of high voltage pulsed current on back extension muscle strengthening and pain. Materials and methods: Forty two patients with back pain syndrome participated in this study. Twenty one patients (mean age 43.62±14.46 years) formed the control group in which hot packs, ultrasound, TENS and exercise program including strengthening and stretching exercises were given. Besides these modalities, high voltage pulsed current and exercise program including strengthening and stretching exercises were given to the study group consisting of 21 patients (mean age 43.81±12.32 years). Results: The difference between within-group parameters was found statistically significant (p<0.05). Multifidus muscle cross sectional area, abdominal muscle strength, flexibility and endurance of back extension muscles were higher in the study group when compared with the control group. However, the difference was not statistically significant (p>0.05). Alleviation in pain level and decrease in Oswestry disability index scores was found statistically significant in the study group when compared with the control group (p<0.05). Conclusion: It was concluded that high voltage pulsed current with exercise is not effective in increasing muscle strength, however it can help to reduce pain and can provide ease in activities of daily living.
Keywords: Back pain; Electric stimulation therapy; Muscle strength